The Principle of Freedom of Contract in Labour Law - Chochova, Maria (Yearbook of the Law Department, 2022)
The civil law principle of freedom of contract is established by the provision of Article 9 of the Bulgarian Act on Obligations and Contracts. In labour law, contractual freedom is further limited by the prohibition to negotiate conditions in the employment contract, which are less favourable for the worker or employee than those established by the collective labour agreement. There is no possibility by collective labour agreements to settle issues of labour and insurance relations of workers and employees, which are regulated by mandatory legal provisions. The collective labour agreement cannot contain clauses, which are less favourable for workers and employees than those established by law or in a collective labour agreement to which the employer is bound.